Digital audio watermarking techniques and technologies applications and benchmarks - Cvejic, Nedeljko; Seppanen, Tapio; Gale Group (Hershey, Pennsylvania Information Science Reference, 2008)
Presents digital audio watermarking as a new and alternative method to enforce intellectual property rights and protect digital audio from tampering. Provides theoretical frameworks, recent research findings, and practical applications.
Introduction to digital audio watermarking -- Spread spectrum for digital audio watermarking -- Audio watermarking through parametric synthesis models -- Robust zero-bit and multi-bit audio watermarking using correlation detection and chaotic signals -- Three techniques of digital audio watermarking -- Advanced audio watermarking based on echo hiding time-spread echo hiding -- Analysis-by-synthesis echo watermarking -- Robustness analysis of patchwork watermarking schemes -- Time-frequency analysis for digital audio watermarking -- Digital audio watermarking techniques for MP3 audio files -- Digital watermarking of speech signals -- Robustness against DA/AD conversion: concepts, challenges and examples -- Subjective and objective quality evaluation of watermarked audio -- watermarking security.
Electronic reproduction.
Keywords: Multimedia systems -- Security measures; Sound -- Recording and reproducing -- Digital techniques; Digital watermarking; Electronic books